RETRACTED: A novel mathematical model for the effects of wall properties on pumping flow of a biofluid in a symmetrical three-dimensional curved duct - Alfwzan, Wafa F.; Riaz, Arshad; Alammari, Maha; Hejazi, Hala A.; Tag El-Din, ElSayed M. (Frontiers in Physics, 2023)
Most pumping actions entail a physical volume change of the duct, which is frequently achieved by having a compliant wall or membrane. To the best of our knowledge, the current study is the first report on a mathematical model developed to analyze the peristaltic transport of a Newtonian fluid in a curved duct with rectangular face and compliant walls. Such geometries are most commonly used in clinical and biological equipment, where the walls of the duct need to be flexible. Flexible ducts are more useful than rigid ones because they do not require any extra modifications or accessories. Here, we have used the conditions of lubrication theory to construct an accurate model, and a common perturbation technique was incorporated to handle the Navier-Stokes equations with emphasis on various aspect ratios and curvatures. A system of curvilinear coordinates operating according to the principles of the cylindrical system was employed to represent the mathematical problem. No-slip boundary limitations were considered at the walls along with the extra constraint of compliant walls showing damping force and stiffness. Comprehensive graphical representations were made to illustrate the effects of all emerging factors of the study in both two- and three-dimensional formats. We found that large curvatures and flexure rigidity decreased the fluid velocity uniformly, but the aspect ratio and amplitude parameters could promote fluid velocity. Validation of the results was performed through the generation of a residual error curve. The current readings were taken again with a straight duct to make a comparison with the existing literature.